Application of oil replenishment and mixed adsorbents technology to enhance the shelf life of frying oil used in chicken drumsticks processing - Innawong, Bhundit; Siasakul, Chatchalai; Udomkun, Patchimaporn (Science, Engineering and Health Studies, 2019)
The effects of mixed adsorbents (bentonite: activated clay: diatomaceous earth in a ratio of 3:4:1 + 1% citric acid) and fresh oil replenishment (10, 20, and 30%) on the physicochemical properties of recycled soybean oil while deep-fat frying chicken drumsticks for 3 days were studied. The used oil with 1% acid value was used as the initial frying medium. Free fatty acid (FFA), peroxide value (PV), dielectric constant (Food Oil Sensor (FOS) reading), and color (L*, a*, b*) were continuously monitored. Using fresh oil replenishment processes with mixed adsorbents significantly resulted in lower FFA, PV, and FOS readings compared to the control. The L*, a*, and b* values of the treated oils were also improved. Application of mixed adsorbents without fresh oil replenishment was not effective in enhancing the physico-chemical qualities of the used oil. Higher replenishment levels resulted in improved oil quality. Replenishment levels at 20 and 30% potentially retarded deterioration of frying oil.